2015
DOI: 10.1177/0009922815588822
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Antimicrobial Resistance Patterns ofEscherichia coliin Children With Urinary Tract Infection in Emergency Department and Primary Care Clinics

Abstract: Higher rates of ampicillin and TMP/SMX resistant urinary E coli isolates were observed among boys and children with a history of genitourinary abnormality. Age and recent antibiotic prescription are also potential risk factors for resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
2
8
0
2
Order By: Relevance
“…A similar trend was observed in our pediatric study as well as the NAUTICA surveillance study of outpatient UTIs [1,14]. The NAU-TICA study reported greater antibiotic resistance to ciprofloxacin, and TMP/SMX among all urinary isolates from US and Canadian male patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A similar trend was observed in our pediatric study as well as the NAUTICA surveillance study of outpatient UTIs [1,14]. The NAU-TICA study reported greater antibiotic resistance to ciprofloxacin, and TMP/SMX among all urinary isolates from US and Canadian male patients.…”
Section: Discussionsupporting
confidence: 87%
“…Ciprofloxacin resistant risk increased exponentially for patients who had > 4 UTIs or had > 5 antibiotic prescriptions in last 6 months. Patients' age, severity of illness, history of multiple hospitalizations, uropathological disorders, comorbidities including obesity, and diabetes are potential explanations for developing such resistance [1,3,6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norfloxacin is a chemical compound of the second generation of fluoroquinolones that had 0.39% resistance to E. coli in our study, which is lower that the results of similar studies conducted by Mullah Abbaszadeh in Tabriz and Heidari Chaleshtari in Shahrekord, which showed resistance rate of 29.01% and 16.30%, respectively. In the research of Heydari Chalesteri et al, Which was conducted in 1995, the highest isolate was E. coli, with the highest resistance to ampicin, tetracycline and sulfamethoxazole, and the least resistance to gentamicin; Also, in the study of Afrug et al In the year 2012, Escherichia coli was the most isolated organism from urine, with a prevalence of 67%, and the highest resistance to sulfamethoxazole and cefalutin (21)(22)(23)(24)(25); this results were consistent with our results. In the study of Taba'i et al (2012)(2013)(2014), The most abundant bacteria isolated from the urine was Staphylococcus aureus with the most resistant to sulfamethoxazole and the least resistance to ciprofloxacin (19); These results were not consistent with our study and studies by Zaidabadi Nejad et al…”
Section: Discussionmentioning
confidence: 99%
“…However, in the intervening period, treatment approaches have become more complicated because of the steady rise in antimicrobial resistance amongst uropathogens, particularly E. coli [57][58][59][60][61], requiring the IDSA and the ESMID to update their conjoint guidelines in 2010 [62]. Although ampicillin was initially the recommended treatment of choice for uncomplicated lower UTI, this is no longer the case because of the very high prevalence of antimicrobial resistance to both amoxicillin and ampicillin worldwide [63][64][65]. However, other B-lactams including cefdinir, cefaclor, amoxicillin-clavulanate and cefpodoxime-proxetil in 3-7 day regimens continue to be recommended for treatment of uncomplicated cystitis when susceptibility is confirmed, and other agents cannot be used [62].…”
Section: Guidelines For Treating Lower Urinary Tract Infectionsmentioning
confidence: 99%